Allelopathic Effect of Artemisia Dubia Extracts on Seed Germination and Seedling Growth of Some Weeds and Winter Crops - Mallik, Baby Babita Das; Acharya, BD; Saquib, M; Chettri, MK (Ecoprint: An International Journal of Ecology, 2015)
Allelopathic effects of aqueous extract of different plant parts (root, stem and leaf) of Artemisia dubia on seed germination and seedling growth of two winter crops (Triticum aestivum and Brassica campestries, and some associated weeds (Bidens pilosa, Ageratum conyzoides, Galinsoga parviflora and Cyperus rotundus) have been investigated in the present study. Extracts of root, stem and leaves of Artemisia dubia showed significant reduction in germination and seedling growth of test crops and weeds. Germination of crop and weed seeds and growth of shoot and root were reduced significantly in test treatments in comparison to the control. The seed germination, shoot length and root length were low at higher concentration. Complete inhibition of seed germination of Ageratum conyzoides, Galinsoga parviflora and Cyperus rotundus at 5 and 10% leaf extract of A.dubia was observed. Allelopathic effects were more pronounced with leaf extract than root or stem extract in most cases.The result indicated difference in allelopathic effect on crop seed and weed seed at higher concentrations. ECOPRINT 21: 23-30, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11901